Lipschütz Ulcer: An Unusual Diagnosis that Should Not be Neglected - Daniela Alexandra Gonçalves Pereira; Eliana Patrícia Pereira Teixeira; Ana Cláudia Martins Lopes; Ricardo José Pina Sarmento; Ana Paula Calado Lopes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract The diagnosis of genital ulcers remains a challenge in clinical practice. Lipschütz ulcer is a non-sexually transmitted rare and, probably, underdiagnosed condition, characterized by the sudden onset of vulvar edema along with painful necrotic ulcerations. Despite its unknown incidence, this seems to be an uncommon entity, with sparse cases reported in the literature. We report the case of an 11-year-old girl who presented at the emergency department with vulvar ulcers. She denied any sexual intercourse. The investigation excluded sexually transmitted infections, so, knowledge of different etiologies of non-venereal ulcers became essential. The differential diagnoses are extensive and include inflammatory processes, drug reactions, trauma, and malignant tumors. Lipschütz ulcer is a diagnosis of exclusion. With the presentation of this case report, the authors aim to describe the etiology, clinical course, and outcomes of this rare disease, to allow differential diagnosis of genital ulceration.